Enhancing Children's Interest and Understanding of Science through STEM Learning at Sekolah Kebangsaan Melayu Raya - Satriyo Nugroho; Muzdalifah Putri Amalia Amin; Relita Kamasi; Ismail Tahir; Ayu Anastasya Rachman; Sucia Pratiwi Tampoy; Rhamal Amir (Transbahasa, 2026)
This study evaluates the effectiveness of implementing STEM (Science, Technology, Engineering, and Mathematics) learning at the preschool level through the “Action of Yeast” and “Electrical Putty” experiments. Pretest and posttest results show a significant increase in children's understanding of the concepts of anaerobic respiration and electrical conductivity. Through an interactive approach, children were actively involved in scientific exploration, which fostered curiosity, courage to experiment, and critical thinking skills. This activity also strengthened social and collaborative skills, where children learned to work together in small groups, appreciate their friends' ideas, and take responsibility for completing experiments. In addition, this practical experience provided an opportunity for KKM-I student participants to apply educational theory in the field, strengthening their pedagogical abilities and understanding the importance of innovation in science learning. This research confirms that the application of STEM-based learning at the preschool level is a strategic step in building a strong foundation for a young generation that is adaptive, creative, and innovative. Thus, this activity not only improves children's scientific understanding but also prepares them to face the challenges of the Industrial Revolution 4.0 era and encourages their interest in science and technology.